A COMPARATIVE STUDY BETWEEN EXTENSIVE READING AND INTENSIVE READING APPROACHES TOWARDS STUDENTS’ VOCABULARY GROWTH TO THE YEAR TWO OF ONE OF THE JUNIOR HIGH SCHOOLS IN KENDARI - Taembo, Maulid (Tirai Edukasi : Jurnal Pendidikan, 2018)
This study investigated a comparative study between extensive reading and intensive reading approaches to find out the differences and which approach is more effective towards students’ vocabulary growth to the year two of one of the junior high schools in Kendari. This study used true experimental design which applied two classes that are given pre-test and post test before and after the exposure to the use of extensive and intensive reading. The populations of this study were the entire second class students of SMP Negeri 10 Kendari. The total students were 190 students. These classes consist of 6 parallel classes and each class consists of 32 or 31 students. All the data were analyzed by using statistical technique; they are descriptive and inferential statistic. Descriptive statistic was used to describe the result of the study for both classes and inferential statistic was used to test the hypothesis. The findings showed that the total of the students’ score under extensive reading was 281.89, while the total of the students’ score under intensive reading was 250.07. Moreover, based on the computation by using t-Test, it shows that t-count = 1.96. It is consulted to the t-table = 1.66. It can be seen that t-count is higher than t-table. It means that there was a significant difference on students’ vocabulary growth under extensive reading and intensive reading approaches. Besides, the mean score of students who were taught under extensive reading was higher than the man score of students who were taught under intensive reading approaches (8.81 > 8.09). It means that the achievement of students under extensive reading was better than the students’ vocabulary achievement under intensive reading approach.